Network defense and countermeasures : principles and practices - Easttom, Chuck (Cybersecurity curriculum., 2024)
Clearly explains concepts, terminology, challenges, tools, and skills Covers key security standards and models for business and government The perfect introduction for all network/computer security professionals and students Welcome to todays most useful and practical introduction to defending modern networks. Drawing on decades of experience, Chuck Easttom brings together updated coverage of all the concepts, terminology, techniques, and solutions youll need to be effective. Easttom thoroughly introduces the core technologies of modern network security, including firewalls, intrusion-detection systems, and VPNs. Next, he shows how encryption can be used to safeguard data as it moves across networks. Youll learn how to harden operating systems, defend against malware and network attacks, establish robust security policies, and assess network security using industry-leading standards and models. Youll also find thorough coverage of key issues such as physical security, forensics, and cyberterrorism. Throughout, Easttom blends theory and application, helping you understand both what to do and why. In every chapter, quizzes, exercises, projects, and web resources deepen your understanding and help you use what youve learnedin the classroom and in your career.